Leitura multimodaI : contribuições para o processo ensino- aprendizagem de Ciências na perspectiva da aprendizagem significativa - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This dissertation investigates how multimodal reading can enhance meaningful learning in the teaching and learning process of science. The study was conducted with coordinators, educators, and students from the 7th year of elementary school and the second stage of Youth and Adult Education (EJA) in four schools within the Goiás State Education Network: a Military School Unit, a Full-Time School Unit, a Part-Time School Unit, and an EJA School Unit. The research draws on the theoretical framework of renowned scholars, including Bakhtin (2011), Britto (2007), Caixeta (2005), Calegari and Perfeito (2013), Dionísio (2006), Jewitt (2009), Kleiman (2008), Kleiman and Moraes (1999, 2003), Kress and Van Leeuwen (2006), and Rojo (2005, 2009, 2012, 2013) in the field of language studies. It also incorporates insights from Sasseron and Carvalho (2008) in science education, along with the contributions of Ausubel (1968, 1978, 1980) and Moreira (2010, 2012-2023) on meaningful learning. The methodology employed includes a literature review, the application of questionnaires, and the development of a Didactic Sequence (DS), which serves as the educational product of this research. The findings reveal that the use of infographics significantly aids in the comprehension of scientific concepts by facilitating the integration of text and images in a cohesive and accessible manner. This approach not only simplifies the assimilation of complex information but also fosters critical analysis of content, promoting learning that extends beyond rote memorization. The study concludes that infographics play a crucial role in developing key skills such as synthesizing information and effectively communicating ideas. Additionally, multimodal reading in science education expands students' scientific knowledge, enhances their ability to critically analyze information from diverse sources, and supports their active and informed participation in society.
Multimodal reading: contributions to the science teaching- learning process from the perspective of meaningful learning
Keywords: Multimodalidade; Infográfico; Sequência Didática; Mapas Conceituais; Multimodality; Infographic; Teaching Sequence; Concept maps; EDUCACAO::ENSINO-APRENDIZAGEM